VALUE BASED MANAGEMENT AT KELOMPOK USAHA BERSAMA (KUBE): English - Sariningsih, Yuce; Anwar, Ali; Mardlhiyah, Aisyah Hasna; Margaretha, Angelique (SAMPURASUN, 2024)
Joint Business Group/Kelompok Usaha Bersama (KUBE) is a business scheme launched in 2010 by the Ministry of Social Affairs for underprivileged families who received social assistance from the Family Hope Program (PKH), with the idea that they will no longer depend on social assistance. KUBE has not yet achieved its goals due to low business management capabilities, weak entrepreneurial culture which has resulted low economic empowerment and performance level. This reason as an urgent need for research and development to analyze phenomena and find solutions for better KUBE performance. The aim of the research is to describe and analyze the value based management at KUBE in Bandung City. This research resulted a new findings related to the stages of determining the assumptions and legal basis used, formulating concepts and proving them into the analytical implementation of KUBE. This implementation was supported by the West Java Provincial Social Service Board in the form of providing data, information on the implementation of KUBE and facilitating the presentation of research reports. The method used is a qualitative approach with TKT at level 3. The main research output is publication on Sinta 1 or Sinta 4 and the additional outputs is a book chapter.